The Correlation Between Vocabulary Mastery and Writing Ability of English Study Club Members - Abdullatif, Rania Abdul Aziz; Suhandra, Ika Rama (English Education Study Program, 2025)
This study aims to investigate the relationship between vocabulary mastery and writing ability among members of the English Study Club. The method used is quantitative with a correlational approach. The sample of the study consisted of 25 members who were selected randomly. Data were collected through vocabulary mastery tests and writing ability tests. The results of the analysis showed that there was a significant positive correlation between vocabulary mastery and writing ability, with a value of r =0.01. This finding indicates that increasing vocabulary mastery contributes to improving writing ability. This study provides recommendations for English teaching to focus more on vocabulary development ini order to improve students' writing ability